Protective factors against self-medication among people with a recent illness who did not seek for attention at a healthcare facility - Virú-Loza, Manuel André (2018)
Introduction: In Peru there is a lack of published studies about self-medication that had been performed nationwide. Most of the information available is descriptive and from small sectors of the population. Objectives: The aim of this study was to analyze if factors related with health services accessibility, perception about disease, doctors and traditional medicine, as well as socioeconomic factors, are associated with selfmedication among people with a recent illness who did not seek for attention at a healthcare facility. Design: Transversal analysis from the National Household Survey (ENAHO) of year 2015. Setting: Nationwide study. Study subjects: Those who had an illness in the last 4 weeks and did not look for attention in a healthcare facility. Interventions: Summary measures were calculated. Bivariate and multivariate logistic regression were used. Results: All variables of interest resulted significant protective factors in both bivariate and multivariate analysis. Conclusions: Variables of interest were significant protective factors, conferring more protection the fact of not having money.